Fish and fish-based products in Timor-Leste’s School Meal Program: Understanding existing use, challenges, opportunities and research needs - Bonis-Profumo, Gianna; Hunnam, Kimberly; Duarte, Agustinha; Pinto, Abelita; Simões, Noviana; Martins, Joaquim; Monteira, Melita; Marques, Epifania; Barreto, Celestino; de Sousa, Alda; Soares, Zulmira; Hayashi, Tomomi; et al. (WorldFish, 2023)
Workshop with government agencies and organisations involved in Timor-Leste’s School Meal Program (PME) shared experiences about using fish in the program and identified focal areas for research. There is wide recognition for the role of aquatic foods and that greater inclusion of aquatic foods in the program requires cooperation and collaboration between partners. Not enough fish is produced in Timor-Leste for domestic supply to meet demand and PME goals. There is a need to build school level capacity for planning, procurement and meal preparation with aquatic foods.